The Emerald handbook of feminism, criminology and social change - Walklate, Sandra; Fitz-Gibbon, Kate; McCulloch, Jude; Maher, JaneMaree (Emerald studies in criminology, feminism and social change, 2020)
Comprehensive and current, this handbook combines a wide range of international contributors to chart the uneasy relationship between feminism, criminology and victimology. It explores both the historical and contemporary questions posed by feminist work and is essential reading for anyone interested in feminism, criminology and social change.